We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
43
3
avatar+1112 

Use the addition method to solve this.

 

 6x + 5y = 2

 

-2x + 7y = 34

 Apr 30, 2019
edited by SmartMathMan  Apr 30, 2019
 #1
avatar+100586 
+2

 

Multiply the bottom  equation through by 3

This gives the system

 

6x +  5y  = 2

-6x + 21y = 102       add these

 

26y  =  104       divide both sides by 26

y = 4

 

And

 

6x + 5(4)  = 2

6x + 20 = 2        subtract 20 from both sides

6x  = -18     divide both sides by 6

x = -3

 

So   { x, y}  =  { -3, 4 }

 

 

cool cool cool

 Apr 30, 2019
 #2
avatar+1112 
+2

I tried it a completely different way, maybe that's why I got it wrong.

SmartMathMan  Apr 30, 2019
 #3
avatar+100586 
0

There is no "set" way to do these, SMM......the idea is to multiply one equation by something so that when we add the result to the other equation, a variable will "drop out".....

 

 

cool cool cool

CPhill  Apr 30, 2019

6 Online Users